FRI0075 Effects of Dmards on Citrullinated Peptide Autoantibody Levels in RA Patients- A Longitudinal Analysis. (15th July 2016) - Schett, G.; Wunderlich, C.; Figueiredo, C.; Cobra, J.F.; Hueber, A.J.; Kleyer, A.; Rech, J.
Abstract : Background: Anti-citrullinated cyclic peptide 2 (CCP2) antibodiy levels are considered to be highly stable during disease-modifying anti-rheumatic drug (DMARD) therapy of rheumatoid arthritis (RA). However, no studies have actually analyzed sequential anti-CCP2 antibody levels during various DMARD therapies in a controll manner Objectives: To study whether stable treatment with DMARDs affects anti-CCP2 antibody levels in patients with rheumatoid arthritis. Methods: In this longitudinal observational study 100 RA patients were followed for anti-CCP2 IgG antibody (U/L) and total IgG level (mg/dL) every 6 months for a total period of 2.5 years. All patients received stable DMARD treatment during this period. Five groups comprising each 20 patients were analysed: (1) methotrexate (MTX) alone, (2) tumor necrosis factor inhibitors (TNFi), (3) tocilizumab (TCZ), (4) rituximab (RTX) and (5) abatacept (ABA). Results: Baseline demographic and disease-specific characteristics were comparable between the 5 groups. Anti-CCP2 antibody levels did not show significant changes in patients treated with MTX (mean±SEM: -24.1±8.1%), TNFi (-14.0±11.1%) or TCZ (-24.3±11.3%) between baseline and the 2, 5 years follow up. In contrast, anti-CCP2 antibody levels significantly decreased during treatment with RTX (-75.6±4.4%) and ABA (-82.5±3.7%). With respect to total IgG levels, no significant changes were observed with MTX (-24.1±8.1%), TNFi (-14.0±11.1%) or TCZ (-24.3±11.3%) over 2, 5 years. In contrast, anti-CCP2 antibody levels significantly decreased during treatment with RTX (-75.6±4.4%) and ABA (-82.5±3.7%). Date for individual patients are summarized in Figure 1. Conclusions: DMARDs targeting the adaptive immune response such as ABA and RTX significantly lowered anti-CCP2 IgG levels, while cytokine inhibitors and methotrexate had no significant effects on anti-CCP2 IgG levels. RTX is the only DMARD, which also lowers total IgG level. Lowering anti-CCP2 IgG levels is a step towards sero-conversion and immunological remission of disease. Disclosure of Interest: None declared